Gamified Mobile Learning for Teaching the Prophet’s Mandatory Traits in Elementary Education - Sakti Chandra Hanafi; Chanifah Indah Ratnasari (Universitas Hamzanwadi, 2026)
The integration of digital media in Islamic elementary education remains limited, particularly in studies that integrate Islamic character education with game-based learning and provide quantitative evidence of learning effectiveness. This study develops and evaluates the usability of an Android-based educational game, Kisah Teladan Rasul, designed to support elementary school students’ understanding of the Prophet’s mandatory traits (ṣidq, amānah, tablīgh, and faṭānah) through gamified mobile learning. A Research and Development approach using the ADDIE model was employed, involving 19 fourth-grade students at SDN Margorejo 2 Pati. The small sample size reflects the exploratory and developmental nature of this study, which prioritizes systematic media development over broad generalizability. Learning improvement was examined through a one-group pretest–posttest design yielding an average N-Gain score of 0.69 (medium category), indicating meaningful improvement in conceptual understanding. Usability was assessed using the System Usability Scale, with a mean score of 90.1, categorized as Excellent (Highly Acceptable). These findings suggest that an Android-based educational game integrating narrative missions, scenario-based challenges, and immediate feedback can serve as effective complementary media in Islamic elementary education. This study contributes by combining systematic instructional design (ADDIE), game-based mobile learning, and empirical usability evaluation within the specific context of Islamic character education.